Design of metallic nickel hollow fiber membrane modules for pure hydrogen separation - Li, Y.; Zhang, M.; Chu, Y.; Tan, X.; Gao, J.; Wang, Shaobin; Liu, Shaomin (John Wiley & Sons, Inc., 2018)
© 2018 American Institute of Chemical Engineers Cost-effective and robust nickel (Ni) membrane for H2 separation is a promising technology to upgrade the conventional H2 industries with improved economics and environmental benignity. In this work, Ni hollow fibers (HFs) with one closed end were fabricated and assembled into a membrane module for pure H2 separation by applying vacuum to the permeate side. The separation behavior of the HF module was investigated both experimentally and theoretically. Results indicate that H2 recovery can be improved significantly by changing the operation conditions (temperature or feed pressure). Ni HF is a promising membrane geometry, but the negative effect of pressure drop when H2 passes through the lumen cannot be ignored. Under the vacuum operation mode, there is little difference in term of H2 recovery efficiency whether the feed gas flow is controlled in countercurrent or recurrent operation. This work provides important insight to the development of superior membrane H2 separation system. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3662–3670, 2018.